Evolution of Cognitive Disorders in Patients with Mild Cognitive Impairment (MCI) After Ischemic Stroke: Secondary Data Analysis from the Improved Health Care in Neurology and Psychiatry—Longer Life (IHCNP) Study - Dragoș-Cătălin Jianu; Ligia Petrica; Traian Flavius Dan; Georgiana Munteanu; Bianca Bora; Sergiu Florin Arnăutu; Sorin Ursoniu; Diana Chira; Ștefan Strilciuc; Cristian Falup-Pecurariu; Dafin Fior Mureșanu (Neurology International)
Background: The Improved Health Care in Neurology and Psychiatry—Longer Life (IHCNP) study was an 18-month prospective, observational, non-interventional research study focused on patients with mild cognitive impairment (MCI) following ischemic stroke. Objectives: Our secondary analysis of the IHCNP data aimed to document the progression of MCI in this patient group. Methods: A total of 100 patients from Romania were recruited, all of whom underwent cognitive assessments using the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Rey Auditory Verbal Learning Test (RAVLT). Clinical evaluations were also conducted as part of the study. Baseline cognitive scores were recorded, and subsequent follow-ups documented cognitive changes over time. Results: At baseline, cognitive scores indicated mild impairment, with averages of MMSE 25.41, MoCA 23.27, and RAVLT 33.63. By the end of the study, patients exhibited a significant cognitive decline, with MMSE scores dropping by 8.7%, MoCA by 10.0%, and RAVLT by 29.5% (p < 0.0001 for all measures), reflecting the progressive nature of MCI post-stroke. Conclusions: These findings highlight the importance of early diagnosis and intervention to mitigate cognitive decline in post-stroke patients. The study underscores the need for ongoing cognitive monitoring to improve patient outcomes and manage MCI progression effectively.